2018
DOI: 10.3389/fphar.2018.01057
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Patient-Tailored, Pharmacist-Led Intervention Program to Enhance Adherence to Antihypertensive Medication: The CATI Study

Abstract: Introduction: Non-adherence to medication is a complex health care problem. In spite of substantial efforts, up till now little progress has been made to effectively tackle the problem with adherence-enhancing interventions. The aim of this study was to investigate the effectiveness of a patient-tailored, pharmacist-led and theory-driven intervention program aimed to enhance self-reported adherence to antihypertensive medication.Materials and Methods: A parallel-group randomized controlled trial in 20 communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…The intensity of antibiotic consumption (IAC) was defined as the cumulative number of defined daily doses (DDDs) of antibiotics in hospitalized patients per 100 patient days in the same period (DDDs/100pd). According to the WHO Collaborative Centre for Drug Statistics Methodology (WHO, 2003), the DDDs equivalence was defined as the usage amount multiplied the pack size divided by the defined daily dose (DDD), a measurement developed by the WHO to compare drug consumption, DDDs = (usage amount × pack size/DDD) (Tang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of antibiotic consumption (IAC) was defined as the cumulative number of defined daily doses (DDDs) of antibiotics in hospitalized patients per 100 patient days in the same period (DDDs/100pd). According to the WHO Collaborative Centre for Drug Statistics Methodology (WHO, 2003), the DDDs equivalence was defined as the usage amount multiplied the pack size divided by the defined daily dose (DDD), a measurement developed by the WHO to compare drug consumption, DDDs = (usage amount × pack size/DDD) (Tang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since the establishment of the system of clinical pharmacists in China in 2002, clinical pharmacists have been increasingly involved in ASPs in hospitals (Xiao and Li, 2013;Li et al, 2017;Zhang et al, 2017). Pharmacist-led interventions have yielded excellent results in many areas (Kooij et al, 2016;van Eikenhorst et al, 2017;Ravn-Nielsen et al, 2018;van der Laan et al, 2018). However, the studies that have been performed on ASPs for hospital inpatients led by pharmacists have received insufficient attention in developing countries (Davey et al, 2017;Sakeena et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the CATI intervention program did not influence self-reported medication adherence, quality of life, illness perceptions or blood pressure. However, participants in the intervention group had stronger beliefs in the necessity of using their medicines after 9 months as compared to the control group ( van der Laan et al, 2018 ). The aim of the present study was to evaluate the cost-effectiveness of the CATI intervention program in comparison with usual care in patients using antihypertensive medication from a societal perspective.…”
Section: Introductionmentioning
confidence: 99%
“…This care consists of reviewing and dispensing of the prescribed medication, providing instructions on its use as well as information about intended effects and possible side effects during first and second dispensing. The CATI study showed no significant effects on self-reported medication adherence or other secondary outcomes [16]. The process evaluation of the CATI study might clarify whether the ineffectiveness of the intervention was due to poor implementation or inadequacies in the design of the intervention.…”
Section: Introductionmentioning
confidence: 99%